2014
DOI: 10.1111/are.12669
|View full text |Cite
|
Sign up to set email alerts
|

Increased gonad growth of the purple sea urchin (Strongylocentrotus purpuratus) fed the giant kelp (Macrocystis pyrifera) and the sea lettuce (Ulva lactuca) enriched with nutrients

Abstract: Increased gonad growth of the purple sea urchin (Strongylocentrotus purpuratus) fed the giant kelp (Macrocystis pyrifera) and the sea lettuce (Ulva lactuca) enriched with nutrients Abstract Adult (Strongylocentrotus purpuratus) purple sea urchins were fed giant kelp (Macrocystis pyrifera) and sea lettuce (Ulva lactuca) macroalgae that were unenriched and enriched with nutrients. Urchins were fed over 10 weeks (5% body weight per day) under laboratory conditions to determine the effect of macroalgae species and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…The GI obtained in our study was not a peak value as in other studies with S. purpurtus ; Azad et al . () noted an increase in GI of 18% when S. purpuratus was fed a diet that contained 21% protein and 41% carbohydrate during 12 weeks, and Cuesta‐Gomez and Sánchez‐Saavedra () found that when M. pyrifera was enriched with nutrients (22% protein; 33% carbohydrate and 4.6% of lipid) this sea urchin showed a gonad increase of approximately 11% in 10 weeks. The factors by which these results were obtained remain unknown, necessitating more feed trials at various times during the year.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The GI obtained in our study was not a peak value as in other studies with S. purpurtus ; Azad et al . () noted an increase in GI of 18% when S. purpuratus was fed a diet that contained 21% protein and 41% carbohydrate during 12 weeks, and Cuesta‐Gomez and Sánchez‐Saavedra () found that when M. pyrifera was enriched with nutrients (22% protein; 33% carbohydrate and 4.6% of lipid) this sea urchin showed a gonad increase of approximately 11% in 10 weeks. The factors by which these results were obtained remain unknown, necessitating more feed trials at various times during the year.…”
Section: Discussionmentioning
confidence: 98%
“…It has been exposed by George, Lawrence, Lawrence and Ford () that prepared feed can support gonadal increase throughout the year and thus solve the problem of low GI due to variability in the biochemical composition of their natural diet (i.e. algae) (Cuesta‐Gomez & Sánchez‐Saavedra ). In this study, no significant differences were found between diets, although gonad weight and GI climbed relative to initial values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The purple sea urchin Strongylocentrotus purpuratus from Baja California, Mexico, is an underexploited resource (Palleiro‐Nayar et al. ) that is now considered a target species for aquaculture (Cuesta‐Gomez and Sánchez‐Saavedra , ). The capture of S. purpuratus remains low because their gonads (or “uni” or “roe”) are not always adequate in size or quality, affecting its commercialization (Explorations Unlimited ; Palleiro‐Nayar et al.…”
mentioning
confidence: 99%